Predictable Variations of the Carbon Sinks and Atmospheric CO2 Growth in a Multi‐Model Framework. Issue 6 (16th March 2021) - Ilyina, T.; Li, H.; Spring, A.; Müller, W. A.; Bopp, L.; Chikamoto, M. O.; Danabasoglu, G.; Dobrynin, M.; Dunne, J.; Fransner, F.; Friedlingstein, P.; Lee, W.; et al.
Abstract: Inter‐annual to decadal variability in the strength of the land and ocean carbon sinks impede accurate predictions of year‐to‐year atmospheric carbon dioxide (CO2 ) growth rate. Such information is crucial to verify the effectiveness of fossil fuel emissions reduction measures. Using a multi‐model framework comprising prediction systems initialized by the observed state of the physical climate, we find a predictive skill for the global ocean carbon sink of up to 6 years for some models. Longer regional predictability horizons are found across single models. On land, a predictive skill of up to 2 years is primarily maintained in the tropics and extra‐tropics enabled by the initialization of the physical climate. We further show that anomalies of atmospheric CO2 growth rate inferred from natural variations of the land and ocean carbon sinks are predictable at lead time of 2 years and the skill is limited by the land carbon sink predictability horizon. Plain Language Summary: Variations of the natural land and ocean carbon sinks in response to climate variability strongly regulate year‐to‐year variations in the growth rate of atmospheric carbon dioxide (CO2 ). Information on the near‐term evolution of the carbon sinks and CO2 in the atmosphere is necessary to understand where the anthropogenic carbon would go in response to emission reduction efforts addressing global warming mitigation. Predictions of this near‐term evolution would thus assist policy‐relevant analysis and carbon management activities. Here we use a set of prediction systems based on Earth system models to establish predictive skills of the ocean and land carbon sinks and to infer predictability of atmospheric CO2 growth rate. We show predictability horizons of up to 6 years for some models for the globally integrated ocean carbon sink, with even higher regional predictive skill. Variations of the land carbon sink are predictable up to 2 years and limit predictability of changes in atmospheric CO2 growth rate at lead time of 2 years. Our study thereby demonstrates an emerging capacity of the initialized simulations for predicting the global carbon cycle and the planet's breath maintained by variations of atmospheric CO2 . Key Points: Predictive skill of the global ocean carbon sink due to initialization is up to 6 years for some models, with longer regional predictability in single models Predictive skill due to initialization for the land carbon sink of up to 2 years is primarily maintained in the tropics and extra‐tropics Anomalies of atmospheric CO2 growth rate are predictable up to 2 years and are limited by the land carbon sink predictability horizon